(untitled) (Research, Society and Development, 2023)
Congenital syphilis is the infection of the fetus by Treponema pallidum, transmitted predominantly transplacentally, at any time during pregnancy or clinical stage of the disease, in an untreated or inadequately treated pregnant woman. It is a preventable and curable disease, closely related to the quality of prenatal care, with low cost for diagnosis and treatment and which generates very high-cost complications for health services and the family. Measures such as partner prenatal care, implemented in 2017, in which a treponemal or non-treponemal test is carried out to detect Syphilis, can function as an important factor in reducing the number of cases of Congenital Syphilis with a view to treating the partner and the non-reinfection of the pregnant woman. Therefore, in this work, we evaluated, through data published in the Department of Informatics of the Unified Health System (DATASUS), the impact of the partner’s Pre-Natal on absolute numbers of Congenital Syphilis in the 5 regions of Brazil, comparing data before and after the implementation of the program with the aim of evaluating its influence on the number of cases of Congenital Syphilis. With this project, it was possible to assess that partner prenatal care is still ineffective as a measure to reduce the number of Congenital Syphilis cases in Brazil.